Aging gracefully: navigating the journey of growing older - Olaolorunpo Olorunfemi; Oluwapelumi Kehinde Irinoye (MGM Journal of Medical Sciences, 2024)
This study aims to explore the concept of aging gracefully, probing beyond just physical appearance to embrace the acceptance of changes that come with age and leading a fulfilled life. This study was conducted through a review of literature from 2018 to 2023 using Google Scholar and other databases and focused on keywords such as “aging gracefully,” “navigating,” and “journey of growing older.” It identified various themes, including the journey of aging, the steps involved in aging gracefully, the significance of embracing aging, and the epigenetic theory of aging, shedding light on how individuals can traverse this path. In conclusion, aging gracefully entails preserving physical health, emotional well-being, and having a good attitude as you age. To accomplish this, we need to stay active with different kinds of workouts, eat a well-balanced diet rich in fruits and vegetables, maintain social connections, and stimulate our brain by engaging in hobbies such as reading and puzzles. Regular check-ups, stress management, skin protection, and healthy behaviors such as getting adequate sleep, reducing alcohol consumption, and quitting smoking are all vital. We should embrace the changes that come with aging and focus on the positive aspects of life to traverse this path gracefully. With this awareness, individuals can face aging with acceptance and vitality, leading life with grace and fulfillment.